Periapical Actinomycosis: A Rare Subdivision of Cervicofacial Actinomycosis, Review of the Literature, and a Case Report - Ramtin Dastgir; Maryam Sohrabi (Hindawi Limited, 2022)
Background. Periapical actinomycosis, which is reckoned as a subgroup of cervicofacial actinomycosis, is an uncommon, more indolent, less invasive, and limited type of actinomycosis infection. However, it can be considerably underreported due to the low number of periapical surgical specimens that are submitted for histopathological analysis after excision of the lesion with the preliminary diagnosis of typical periapical infections. It is believed that during root canal treatment, the organisms are displaced from the oral cavity into the periapical regions as a result of failure to establish aseptic techniques which can further result in actinomycosis infections and, in rare instances, lead to more severe events and can even be life-threatening. Case Presentation. We intend to report a case of periapical actinomycosis in a 34-year-old female who presented with the chief complaint of pain and slight mobility of the mandibular right second premolar and first molar with no significant issues in the patient's medical history. Initial orthopantomography revealed a uniloculated, radiolucent lesion engulfing the apices of the aforementioned teeth. An incisional biopsy was then obtained which revealed fragments of fibroconnective tissue including few crushed bone particles severely infiltrated by acute inflammatory cells and some foamy macrophages. The suppurative exudate focally surrounds colonies of filamentous bacteria as round basophilic masses with radial configuration resembling "sulfur granules." Surgical approach consisted of curettage accompanied with peripheral ostectomy and cautious burnishing of the two involved tooth roots. Conclusion. This case report emphasizes the importance of aseptic techniques during endodontic and more invasive treatments, as they can cause penetration of Actinomyces into the periapical region which in some cases can lead to more serious complications and even life-threatening situations.